2020
DOI: 10.3991/ijet.v15i21.17345
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Enjoyment Element in Health-Related Game-Based Learning

Abstract: Educational games are often used as teaching and learning tools, with studies showing that game-based learning is widely accepted among children and teenagers. The experience of enjoyment typically associated with playing games provides for a deeper learning experience and allows the individual to connect various concepts, skills, and knowledge, as well as sparking creativity. This paper builds upon previous studies of enjoyment in health-based gaming and aims to articulate a definition of enjoyment in gaming.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…In the last 10 years, the idea of enjoyment in play has received much attention from scholars (Ab Jalil et al, 2020). San Frutos and Esteban (2022) argued that one of the key features of play relates directly to enjoyment.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Secondly, they lead to increased learning outcomes by improving knowledge acquisition [109], understanding and retention [18,112], critical thinking [90,106], perception [72], and creativeness [11]. Thirdly, increased motivation [70], enjoyment [55], satisfaction [17], involvement [29], and flow [67] are among the motivational outcomes of serious games.…”
Section: Serious Gamesmentioning
confidence: 99%
“…Serious games are also utilized for motivational outcomes. Satisfaction [17], positive attitudes towards the game [109], enjoyment [55,70], immersion [29], and flow [67] are among the motivational outcomes supported by serious games. Some of the identified design approaches aim to promote the motivational outcomes of serious games.…”
Section: Design Approaches For Motivational Outcomesmentioning
confidence: 99%